Is pulmonary artery wedge pressure a reliable surrogate of left ventricular end-diastolic pressure during exercise for diagnosing HFpEF in patients with unexplained dyspnea?. (3rd October 2022) - Caravita, S; Baratto, C; Gallone, G P; Faini, A; Dewachter, C; Senni, M; Badano, L P; Vachiery, J L; Parati, G
Abstract: Background: Left ventricular end-diastolic pressure (LVEDP) is the gold-standard for the assessment of LV filling pressure. For practical reasons, pulmonary artery wedge pressure (PAWP) is used as a surrogate for LVEDP. However, the interposition of the left atrium (LA) may account discrepancies between LVEDP and PAWP. The imprecision of both end-diastolic (or mid-A) and mean PAWP estimates for LVEDP has been widely described for cardiac catheterization at rest. PAWP measurement during exercise has been advocated to discriminate heart failure with preserved ejection fraction (HFpEF) from non-cardiac dyspnea, with an end-expiratory pathologic threshold ≥25 mmHg. However, a formal comparison of PAWP (either mid-A or mean PAWP) vs LVEDP during exercise has never been performed. Aim: To compare LVEDP and PAWP during exercise. Methods: We retrospectively analyzed consecutive patients with unexplained dyspnea and a normal LV ejection fraction, who had a clinical indication of right and left heart catheterization at rest and during exercise to assess unexplained dyspnea. Patients with mitral regurgitation ≥ moderate were excluded. Hemodynamic measurements were always taken at end-expiration. Results: Forty-six consecutive patients were included in the analysis (80% with a peak mean PAWP ≥25 mmHg). We found a good correlation between both mid-A and mean PAWP on one side, and LVEDP on the other side (R2>0.55). At peak exercise, mid-A PAWP had no bias as compared with LVEDP, while mean PAWP slightly overestimated LVEDP by 1–2 mmHg. However, confidence intervals were quite large (Figure 1), suggesting imprecision of PAWP estimates for LVEDP in the individual patient. A disagreement between mean PAWP and LVEDP, using a threshold of ≥25 mmHg for both variables at peak exercise, was found in 11% of patients. In 4% of them, mean PAWP was ≥25 but LVEDP <25 mmHg, due to the appearance of tall V waves in the PAWP position (LA stiffness), increasing PAWP above LVEDP. In the remaining 7%, LVEDP was ≥25 but PAWP <25 mmHg. The latter patients, in whom HFpEF would have not been diagnosed based on peak PAWP alone, showed a PAWP increase during exercise relative to cardiac output changes (PAWP/CO slope) >2 mmHg/L/min, as an alternative parameter suggesting HFpEF. Conclusions: In patients with unexplained exertional breathlessness, both mid-A and mean PAWP showed good correlation with LVEDP during exercise with minimal average bias, but their ability to estimate LVEDP was burdened by a relevant imprecision. Therefore, when in these patients peak PAWP is <25 mmHg, its assessment might need to be complemented by additional measurements (including LVEDP or PAWP/CO slope) to maximize the diagnostic power of exercise cardiac catheterization in identifying HFpEF. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship.